2020
DOI: 10.15252/embj.2019103255
|View full text |Cite
|
Sign up to set email alerts
|

Secreted stromal protein ISLR promotes intestinal regeneration by suppressing epithelial Hippo signaling

Abstract: The Hippo–YAP signaling pathway plays an essential role in epithelial cells during intestinal regeneration and tumorigenesis. However, the molecular mechanism linking stromal signals to YAP‐mediated intestinal regeneration and tumorigenesis is poorly defined. Here, we report a stroma–epithelium ISLR–YAP signaling axis essential for stromal cells to modulate epithelial cell growth during intestinal regeneration and tumorigenesis. Specifically, upon inflammation and in cancer, an oncogenic transcription factor E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
(46 reference statements)
1
35
0
Order By: Relevance
“…The matrix-mediated integrin signalling via YAP/TAZ mechano-transduction promotes intestine regeneration in collagen type I; this process is accompanied by Wnt activation, and the same phenomenon was observed in human ulcerative colitis [44]. ISLR has been identified as a marker of mesenchymal stromal cells [45] because it can downregulate Hippo signals for YAP activation to promote intestine regeneration [46]. Mesenchymal stem cells (MSCs) have a significant therapeutic potential for tissue damage by improving the growth of intestinal crypts in vitro by activating the Wnt/β-catenin signalling pathway [47].…”
Section: Stromal Cells Inflammatory Cells and Cytokine Mediators Invmentioning
confidence: 70%
“…The matrix-mediated integrin signalling via YAP/TAZ mechano-transduction promotes intestine regeneration in collagen type I; this process is accompanied by Wnt activation, and the same phenomenon was observed in human ulcerative colitis [44]. ISLR has been identified as a marker of mesenchymal stromal cells [45] because it can downregulate Hippo signals for YAP activation to promote intestine regeneration [46]. Mesenchymal stem cells (MSCs) have a significant therapeutic potential for tissue damage by improving the growth of intestinal crypts in vitro by activating the Wnt/β-catenin signalling pathway [47].…”
Section: Stromal Cells Inflammatory Cells and Cytokine Mediators Invmentioning
confidence: 70%
“…Islr was previously shown to maintain an undifferentiated state of stromal cells ( Maeda et al, 2016 ). In this study, Xu et al (2020) found that Islr inhibits Lats, leading to increased Yap activity. They then used a stromal cell conditional KO mouse model targeting Islr, in order to understand its role in modulating the Hippo signaling pathway during homeostasis and damage.…”
Section: How Differentiated Is Too Much Differentiation—is There Any mentioning
confidence: 72%
“… Romera-Hernández et al (2020) induced intestinal injury using methotrexate, and found that group 3 innate lymphoid cells (ILC3s) drive intestinal epithelial repair in a Yap1 dependent manner, but independent of intestinal regenerative IL-22. Xu et al (2020) examined the role of the stromal cell protein ISLR [immunoglobulin (Ig)-like domain and five leucine-rich repeat (LRR) domains], in recovery from DSS and TNBS injury in mice. Islr was previously shown to maintain an undifferentiated state of stromal cells ( Maeda et al, 2016 ).…”
Section: How Differentiated Is Too Much Differentiation—is There Any mentioning
confidence: 99%
“…H&E staining, immunofluorescence, IHC and western blotting were performed as we previously described 31 . The BAT was rinsed with PBS, fixed in 4% PFA, paraffin-embedded, sectioned at 5 μm and stained with H&E. For immunohistochemical staining, antigen retrieval was performed by heating the slides to 95 °C for 20 min in 0.01 M citrate buffer (pH 6.0) in a microwave.…”
Section: Methodsmentioning
confidence: 99%